HUBUNGAN AKTIVITAS FISIK DAN STRES TERHADAP KUALITAS TIDUR SELAMA PANDEMI COVID-19 PADA MAHASISWA TINGKAT 2 FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020-2021 - Danisa Agustien Nurrachmawati (2022)
Student activities in lectures involve many physical activities that affect student stress during the lecture. Physical activity during Covid-19 is very limited in breaking the chain of transmission, by not leaving the house and gathering each other. The researchers' goal was to understand the relationship between stress and physical activity in sleep quality during the Covid-19 period in level 2 students. Physical activity was measured by the International Physical Activity Questionnaire, stress was measured by the Perceived Stress Scale, and sleep quality through the Pittsburgh Sleep Quality Index. Cross-sectional research design using google form questionnaire disseminated to 2nd grade students, which was taken simply random sampling. Based on data obtained by students with heavy physical activity experienced poor sleep quality 87.7% and moderate category stress 88.9% who had poor sleep quality. The results of the chi-square test had no association between physical activity and stress and sleep quality.